2021
DOI: 10.1002/jmv.27494
|View full text |Cite
|
Sign up to set email alerts
|

Advances in laboratory detection methods and technology application of SARS‐CoV‐2

Abstract: At present, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is raging worldwide, and the coronavirus disease 2019 outbreak caused by SARS-CoV-2 seriously threatens the life and health of all humankind. There is no specific medicine for novel coronavirus yet. So, laboratory diagnoses of novel coronavirus as soon as possible and isolation of the source of infection play a vital role in preventing and controlling the epidemic. Therefore, selecting appropriate detection techniques and methods is parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…47 Of course, if conditions permit, the detection and evaluation of antibody titers before vaccination will undoubtedly make this study more targeted. 48 The timing of the booster may also need to be shorter than 6 months.…”
Section: The Objectives Of Covid-19 Booster Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Of course, if conditions permit, the detection and evaluation of antibody titers before vaccination will undoubtedly make this study more targeted. 48 The timing of the booster may also need to be shorter than 6 months.…”
Section: The Objectives Of Covid-19 Booster Vaccinationmentioning
confidence: 99%
“…The United Kingdom Joint Committee on Vaccination and Immunization suggested that people with immunodeficiency (including patients with advanced HIV, leukemia, organ transplantation, or immunosuppressive drugs) should be taken as the targets of a booster vaccination 47 . Of course, if conditions permit, the detection and evaluation of antibody titers before vaccination will undoubtedly make this study more targeted 48 . The timing of the booster may also need to be shorter than 6 months.…”
Section: The Objectives Of Covid‐19 Booster Vaccinationmentioning
confidence: 99%
“…At present, the gold standard of COVID‐19 diagnosis is nucleic acid detection of SARS‐CoV‐2, which needs to be performed by specialized personnel in a polymerase chain reaction (PCR) laboratory with a second‐class biosafety level. 16 , 17 , 18 , 19 Therefore, it cannot be widely promoted due to the high requirements of staff skills and site requirements, especially in some grassroots medical institutions. In addition, it takes 4–6 h to complete the whole detection process of SARS‐CoV‐2 nucleic acid detection, and it takes a longer time when the number of specimens is large, leading to delays in the identification of COVID‐19 patients in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is a public health emergency with the fastest transmission speed, the broadest range of infection, and the most challenging prevention and control in the past 100 years ( Ye et al, 2020a , 2021 ; Chen et al, 2021 ; Tian et al, 2021a , b ; Han and Ye, 2022 ; Zhang et al, 2022 ), and it can cause multiple organ damage or even death ( Tian and Ye, 2020 ; Ye et al, 2020a , b , c ; Han and Ye, 2021 ; Han et al, 2021 ; Khodavirdipour et al, 2021a , b ; Tian et al, 2021b ). Vaccines and drugs are being developed ( Khodavirdipour et al, 2020 , 2021c , 2022 ; Khodavirdipour, 2021 ).…”
Section: Introductionmentioning
confidence: 99%